Silicon modulate the non-enzymatic antioxidant defence system and oxidative stress in a similar way as boron in boron-deficient cotton flowers - Souza Junior, Jonas Pereira de [UNESP]; Prado, Renato de Mello [UNESP]; Silva Campos, Cid Naudi; Sousa Junior, Gilmar da Silveira [UNESP]; Costa, Milton Garcia [UNESP]; de Pádua Teixeira, Simone; Gratão, Priscila Lupino [UNESP] (Elsevier, 2023)
Silicon (Si) application, especially via foliar application, may be promising to attenuate oxidative damage, as Si can improve the non-enzymatic antioxidant system of cotton flowers. However, studies that address the relationship between boron (B) and Si in cotton flowers are still scarce. Therefore, this paper aimed to evaluate the effect of silicon alone and added to the borate solution applied via foliar spray on the oxidative stress; proline, carotenoid, and phenol contents; and biomass production of cotton flowers grown under moderate B deficiency. The experiment was arranged in a completely randomized design with ten replicates and the following five treatments: control (cotton plants under boron deficiency); water application (without B and Si); boron application; silicon application; and B + Si. The application of B, Si, and B + Si reduced the malondialdehyde content in cotton petals by 45%, 48%, and 59%, respectively, and in cotton anthers by57%, 64%, and 67%, respectively. The dry matter of cotton petals in the respective treatments increased by 20%, 16%, 35%, and 44%, while the dry matter of cotton anthers increased by 40%, 24%, 48%, and 53%, respectively, compared to the treatment with water only. There was a strong relationship between B content and dry matter; Si content and the contents of phenols and proline; and carotenoid content and the contents of MDA and H2O2. B deficiency can induce oxidative stress specifically in the petals and anthers of cotton, with carotenoids being the main defense mechanism in flowers, while Si is capable of strongly activating defense mechanisms from phenol and proline. In conclusion, the development of organs related to reproduction is impaired by B deficiency. In addition, the foliar application of Si and B attenuates the effects of oxidative stress on the sepals and anthers of cotton, mainly favoring the development of cotton anthers.
Keywords: Abiotic stress; Beneficial element; Gossypium hirsutum; Micronutrient deficit; Reproductive development